2023
DOI: 10.1021/acs.jafc.2c08523
|View full text |Cite
|
Sign up to set email alerts
|

Alleviating Effect of Lacticaseibacillus rhamnosus 1.0320 Combined with Dihydromyricetin on Acute Alcohol Exposure-Induced Hepatic Impairment: Based on Short-Chain Fatty Acids and Adenosine 5′-Monophosphate-Activated Protein Kinase-Mediated Lipid Metabolism Signaling Pathway

Abstract: Excessive drinking has been listed by the World Health Organization as the fifth major risk factor; especially the liver, as the core organ of alcohol metabolism, is prone to organic lesions. Probiotics have received attention due to their bioactivity for liver protection. The beneficial effects of probiotics on hosts are related to their physiological functions. Therefore, based on the concept of second-generation synbiotes, this study explored the protective effects of four dietary polyphenols on the stress … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Probiotics and polyphenols are scarcely evaluated in combination despite being consumed together regularly (e.g., yogurt and fruits). However, the scientific literature is beginning to evaluate novel formulations of polyphenol-enriched probiotic yogurts ( Walter et al, 2021 ) and nutraceuticals ( Sampaio et al, 2023 ), and there is evidence of the beneficial effect of their combination on conditions ( Wang et al, 2023 ). In this study, we evaluated these biocompounds as a potential strategy for intestinal free-fatty acid removal.…”
Section: Discussionmentioning
confidence: 99%
“…Probiotics and polyphenols are scarcely evaluated in combination despite being consumed together regularly (e.g., yogurt and fruits). However, the scientific literature is beginning to evaluate novel formulations of polyphenol-enriched probiotic yogurts ( Walter et al, 2021 ) and nutraceuticals ( Sampaio et al, 2023 ), and there is evidence of the beneficial effect of their combination on conditions ( Wang et al, 2023 ). In this study, we evaluated these biocompounds as a potential strategy for intestinal free-fatty acid removal.…”
Section: Discussionmentioning
confidence: 99%
“…Lactic acid bacteria (LAB) are critical probiotics that confer health benefits to the host, such as antioxidant and anti-inflammatory activities, amelioration of liver injury, immunoregulation, and regulation of gut microbiota. , A recent study has reported that Lacticaseibacillus rhamnosus combined with dihydromyricetin alleviated acute alcohol-induced hepatic injury . Some probiotics, including Lacticaseibacillus casei, Bifidobacterium lactis, and Lactiplantibacillus plantarum, are effective in alleviating host inflammation in mice. , The exciting effectiveness of LAB treatment has been reported, considering the strain-specific functions and diverse mechanisms, suggesting that studying the contribution of specific LAB to the progression of hepatic or intestinal injury could unearth effective treatment options.…”
Section: Introductionmentioning
confidence: 99%
“…DHM could also increase serum GLP-1 level and enhance exercise endurance in aerobic exercise mice (L et al , 2022), indicating that DHM may play a role in preventing and treating chronic diseases by regulating gut microbiota or its metabolites to increase GLP-1 level in vivo. Published literatures indicated that DHM combined with L. rhamnosus 1.0320 restored the intestinal barrier induced by acute alcohol exposure by upregulating the intestinal short-chain fatty acid levels (Wang et al, 2023a). However, the underlying molecular mechanism involved with the enhancement of GLP-1 by DHM administration remains to be further elucidated.…”
Section: Introductionmentioning
confidence: 99%